Organizational Culture and Its Role in Shaping a Supportive Work Environment for Teachers - Nugroho, Murwanto Setyo; Harsono, Harsono; Rohmah, Wafrotur (Yayasan Keluarga Guru Mandiri, 2026)
This study aims to examine the role of organizational culture in shaping a supportive work environment for teachers in secondary schools. Using a quantitative, descriptive-explanatory design, the research surveyed 52 teachers from a public junior high school in Sukoharjo, Indonesia. Data were collected using validated instruments measuring shared values, norms and expectations, communication practices, and emotional support, then analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The results show that shared values (? = 0.422), norms and expectations (? = 0.386), and communication practices (? = 0.401) have a significant, positive influence on emotional support, which, in turn, directly affects the supportive work environment (? = 0.477). These findings demonstrate that organizational culture is not merely symbolic but functions as a strategic determinant of teachers’ psychological well-being and job satisfaction. The study addresses the research problem by providing empirical evidence that organizational culture significantly influences educators' emotional climate and professional sustainability. It contributes to educational management theory by integrating cultural constructs into a practical framework for policy development. Future research is recommended to include variables such as leadership style, workload, and reward systems to broaden the understanding of how internal school dynamics influence teacher well-being.